1981
DOI: 10.1099/00207713-31-3-327
|View full text |Cite
|
Sign up to set email alerts
|

Acidiphilium cryptum gen. nov., sp. nov., Heterotrophic Bacterium From Acidic Mineral Environments

Abstract: Acidiphilium gen. nov. is comprised of gram-negative, aerobic, mesophilic, rodshaped bacteria that grow in lean organic media between pH 1.9 and 5.9 but not at pH 6.1, Small amounts of organic substrates are required for growth, but high concentrations inhibit growth, especially the organic digests used in conventional bacteriological media. Sodium acetate is strongly inhibitory at a concentration of 0.01%. Endospores are not formed, and some strains are motile by means of one polar flagellum or two lateral fl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
96
1

Year Published

1986
1986
2015
2015

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 158 publications
(102 citation statements)
references
References 7 publications
5
96
1
Order By: Relevance
“…and coal mine drainage (20,27), and cultures of Thiobacillus ferrooxidans (5)(6)(7)(8)(9)11,18,36,37). Harrison (6) studied systematically acidophilic, mesophilic, heterotrophic bacteria derived directly from coal strip-mine refuse and also as contaminants in cultures of T. ferrooxidans, and proposed the designation of the genus Acidiphilium for these bacteria.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…and coal mine drainage (20,27), and cultures of Thiobacillus ferrooxidans (5)(6)(7)(8)(9)11,18,36,37). Harrison (6) studied systematically acidophilic, mesophilic, heterotrophic bacteria derived directly from coal strip-mine refuse and also as contaminants in cultures of T. ferrooxidans, and proposed the designation of the genus Acidiphilium for these bacteria.…”
mentioning
confidence: 99%
“…Harrison (6) studied systematically acidophilic, mesophilic, heterotrophic bacteria derived directly from coal strip-mine refuse and also as contaminants in cultures of T. ferrooxidans, and proposed the designation of the genus Acidiphilium for these bacteria. The genus Acidiphilium now consists of five species, A. cryptum (6), A. organovorum (18), A. angustum (36), A. facilis (36), and A. rubrum (36). Recently, Kishimoto et al (13) have reported Acidobacterium capsulatum, a new acidophilic heterotrophic bacterium isolated from acidic mineral environments.…”
mentioning
confidence: 99%
“…The following strains of acidophilic chemoorganotrophic bacteria were studied: Acidiphilium cryptum ATCC 33463 10) , Acidiphilium organovorum ATCC 43141 23) , Acidiphilium multivorum JCM 8867 39) , Acidocella facilis ATCC 35904 19,40) , Acidocella aminolytica JCM 8796 18,19) , and Acidobacterium capsulatum JCM 7670 17) . The strains with ATCC and JCM numbers were obtained, respectively, from the American Type Culture Collection (Rockville, MD) and Japan Collection of Microorganisms (Wako, Japan).…”
Section: Test Organismsmentioning
confidence: 99%
“…Thus, the isolation of Thermosulfobacterium commune (Zeikus et al, 1983) during ecological studies of decomposing algal bacterial mats associated with hot aquatic habitats in Yellowstone National Park led to the discovery of an organism with a highly unusual combination of biochemical, chemical, physiological and structural properties. Other very unusual bacteria isolated from 'exotic' habitats include AcetoanaerobMm (Sleat, Mah and Robinson, 1985), Acidophilus (Harrison, 1981), Dictyoglomus (Saiki et al, 1985), Erythrobacter (Shiba and Simidu, 1982), Methanothermus , Stella (Vasilyeva, 1985), Thermococcus (Zillig et al, 1983) and Thermoproteus . At the other extreme, many newly isolated actinomycete species, such as Dactylosporangiurn roseutn , Microbispora viridis (Miyadoh et al, 1985) and Streptomyces sulfonofaciens (Miyadoh et al, 1983), differ from established species by little other than their ability to produce a novel secondary metabolite.…”
Section: Computer-assisted Identificationmentioning
confidence: 99%